Determinants of Reasons for Financial Disagreements in Married or Cohabiting Couples in Russia: Relational Sociology Approach - Zhidkova, Polina (Экономическая социология, 2022)
At present, research on financial disagreements is extensive but general. There are no studies of financial conflicts in Russian families. Taking into consideration the values of partners in dyadic relationships by utilizing relational sociology framework, the study explores five types of financial disagreements: (i) value conflict, (ii) conflict over price, (iii) conflict over necessity, (iv) goal conflict, and (v) conflict over income, in order to detail the structure and the various reasons behind conflicts about money in Russian families; and aims to understand the determinants behind each type. The analysis was built on the 2018 wave of the Survey of Consumer Finance that presents dyadic data for 3,503 Russian couples. Regression models were calculated for men and women separately to identify gender effects. All the considered reasons for financial disagreements are caused in part by partners’ different attitudes towards money. In addition, the increase in women’s share of family income increases the likelihood of conflict over price; traditionalist attitudes correlate with an increase in goal conflict; and conflict over income is connected with dissatisfaction with the decision-making process. The study shows the significance of considering partners’ values for the analysis of a family’s financial situation.